Quantifying microscale drivers for fatigue failure via coupled synchrotron X-ray characterization and simulations - Sven Gustafson (Nature Portfolio, 2020)
Structural alloys have distinct microstructural features known as twins that are preferential sites for fatigue crack initiation and need to be better understood to mitigate catastrophic failures. Here, the authors show unusually large stress gradients near a twin boundary, using X-ray techniques and modelling.